Correlación de variables climáticas (temperatura y precipitación) con el índice de cobertura vegetal con el método ndvi en la zona noroccidental de la provincia de Cotopaxi en el piso bioclimático, bosque siempreverde montano de la cordillera occidental de los andes (bsmn03) entre 2000 y 3100 m.s.n.m. - Saquinga Tituaña, Carlos Enrique (2020)
This research project has been carried out in the bioclimatic floor: "Bosque Siempre Verde Montano" of the Western mountain range of the Andes that is located in the El Tingo Parish, Pujilí Canton in which the possible influence of climate change on the development of plant species was studied; a bibliographic review has been used where data from the INAMHI meteorological yearbooks have been extracted from the climatic variables (temperature and precipitation), that have used to generate two Gaussen Diagrams where the climatic fluctuation of the place is shown graphically. Vegetation cover maps of the years 1990, 2008 and 2016 were made with the help of shapes by the use of the NDVI method, which demonstrates the loss of vegetation cover that has occurred temporarily; therefore, in this investigation a correlation of climatic variables is made with the generated images where it is established that when comparing the maps of the years 1990 and 2008 there is a loss of the vegetation cover of 12.71%, the same that becomes mosaic agricultural, taking into account that the climatic variability is minimal since the climatic conditions of temperature and precipitation remained stable, but when comparing the maps of the years of 2008 and 2016, there is again loss of native vegetal cover in 3.31%; the climatic variability remains soft with rainfall during 12 months of the year and with right conditions so that, the vegetation can be restored albeit the loss of the diversity in this period of time is observed to a lesser extent, this may be due to the fact that there was a partial process of anthropic abandonment of the forested area so nature is affected at a lower level, so the researcher can ensure that this bioclimatic floor the activity of man has played a very important role in the loss of local biodiversity, unlike the climate that has not contributed to such change, so it is crucial that the population has knowledge on this issue so that it can contribute to the conservation of plant species in the sector.